Analisis Penerapan Sistem Informasi Akuntansi Terhadap Penjualan E-Ticket Menggunakan Aplikasi Kai Access (Studi Kasus Pada Pt. Kereta Api Indonesia Medan) (Jurnal Kendali Akuntansi, 2023)
This study aims to understand the implementation of the accounting information system on electronic tickets with the KAI Access application at the Medan train station and to understand whether the internal control system of the accounting information system at the Medan station works efficiently or not. PT. Kereta Api uses an electronic ticket accounting information system (e-ticketing) as a form of improving the quality of service and security for users, especially improving the quality of information, the information provided must be useful, reliable and used in a timely manner. The method used in this study is a field study which includes observation, interviews and documentation. This study uses qualitative methods and data analysis techniques are applied, namely descriptive analysis. The results of the analysis and interpretation of data on the implementation of the electronic ticketing (e-ticketing) Accounting Information System at PT Kereta Api are an integrated system. Organizational structure of PT. Railways are generally very good and prevented from manipulation. PT. Kereta Api runs electronic ticketing operations (e-ticketing) using serial documents, accounting records including deposit books, income analysis, expense analysis, cash register books, and joint books. Implementation of electronic ticket accounting information systems (e-ticketing) for PT. Railways are considered good until the implementation of internal control is also running effectively.